Publisher Correction: Upper critical field and superconductor-metal transition in ultrathin niobium films - Zaytseva, Iryna; Abaloszew, Aleksander; Camargo, Bruno C.; Syryanyy, Yevgen; Cieplak, Marta Z. (Scientific reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.